The effect of bio-fertilization and nitrogen fertilizer spraying on some growth traits and yield of two hybrids of chilli pepper (Capsicum annuum L.) - Farhan, S.S.; Mutar, K.A. (Journal of Kerbala for Agricultural Sciences, 2024)
This study was conducted to determine the role of azotobacter bacteria and nitrogen fertilizer in the growth and yield of two hybrids of chilli pepper. The experiment included two factors: the first factor was two hybrids of chilli pepper (Barbarian and Hyffa), while the second factor was the fertilizer treatments, which consisted of eight treatments: the controle treatment, spraying with distilled water (T1), inoculation with the Azotobacter biofertilizer (T2), spraying urea fertilizer at a concentration of 150 mgl-1 (T3), spray urea fertilizer at a concentration of 300 mgl-1 (T4), spray urea fertilizer at a concentration of 450 mgl-1 (T5), Azotobacter + spraying urea fertilizer at a concentration of 150 mgl-1 (T6), Azotobacter + spraying urea fertilizer at a concentration of 300 mgl-1 (T7), and Azotobacter + spraying urea fertilizer at a concentration of 450 mgl-1 (T8). The experiment carried out according to a split plot system design within a randomized complete block design(RCBD) with three replications. The first factor (hybrid) placed in the main plots and the second factor (fertilizer treatments) was placed in the sub-plots. The means compared according to the least significant difference test. (L.S.D) at a probability level of 5%. The results can summarized as follows: The interaction treatment between the fertilizer treatments and the chilli pepper hybrid (T8×Barbarian) showed significant superiority in most of the studied indicators compared to the other interaction treatments and gave the highest values in the percentage of elements in the leaves: Nitrogen (3.021%), Phosphorus (0.567%), Potassium (3.791%). It excelled in indicators of vegetative growth and chlorophyll content in leaves (362.1 mg 100 g - 1 fresh weight). It also excelled in quantitative indicators of yield represented by fruit weight (33.66 g), number of fruits (34.16 fruits Plant-1), and plant yield (1.149 kg plant-1), and it also excelled in the qualitative indicators of the fruits and their vitamin C content (121.3 mg 100 g-1 ).